A Pattern Recognition Receptor C-type Lectin-S6 (CTL-S6) is Involved in the Immune Response in the Silkworm (Lepidoptera: Bombycidae). Issue 1 (29th January 2021) - Shen, Dongxu; Tong, Meijin; Guo, Jiyun; Mei, Xianghan; Xia, Dingguo; Qiu, Zhiyong; Zhao, Qiaoling
Abstract: Insect innate immunity is initiated by the special recognition and binding of the foreign pathogens, which is accomplished by the pattern recognition receptors (PRRs). As an important type of PRRs, C-type lectins (CTLs) play various roles in insect innate immunity, including pathogen recognition, stimulation of prophenoloxidase, regulation of cellular immunity and so on. In this study, we have cloned the full-length cDNA of a CTL gene named CTL-S6 from the silkworm, Bombyx mori . The open reading frame (ORF) of B. mori CTL-S6 encodes 378 amino acids, which contain a secretion signal peptide. The mRNA of CTL-S6 exhibited the highest transcriptional level in the midgut. Its transcriptional level increased dramatically in fat body and hemocytes upon Escherichia coli or Micrococcus luteus challenge. Purified recombinant CTL-S6 could bind to bacterial cell wall components, including peptidoglycan (PGN, from Bacillus subtilis ) and lipopolysaccharide (LPS, from E. coli 0111:B4), and recombinant CTL-S6 was involved in the encapsulation and melanization of hemocytes. Furthermore, the addition of recombinant CTL-S6 to the hemolymph of silkworm resulted in a significant increase in phenoloxidase activity. Overall, our results indicated that B. mori CTL-S6 may serve as a PRR for the recognition of foreign pathogens, prophenoloxidase pathway stimulation and involvement in the innate immunity.